Exploring the COMFORT model for complex communication for physiotherapists in neurorehabilitation: a critical review - Pelaez, Selma; Hall, Michelle C. (Opast Group, 2017)
Literature has evaluated the level of accomplishment of the Patient-centred care (PCC) model from physiotherapists working in Neurorehabilitation. Reviewing the literature has revealed a lack of kills, confidence and training by physiotherapists to communicate difficult or complex information, such as poor prognosis or shared goal- setting, leading patients and families to complain about the need for more empathy, encouragement for patients to foster autonomy and rapport with physiotherapists. This problem is not unique to physiotherapists in neurorehabilitation and can be found in other medical disciplines. Many frameworks have been designed in order to teach how to successfully lead communication in stressful situations. However, the COMFORT model, which is an acronym for seven key principles of effective communication, is a grounded framework based on PCC ideals.